Epidemiological characteristics of orthopedic trauma patients admitted to emergency department in Coronavirus disease 2019 pandemic: A retrospective and comparative study (Annals of Medical Research, 2022)
Aim: The aim of the present study was to compare the data and epidemiological characteristics of orthopedic trauma patients who presented to the emergency room in the period of pandemic year with the year before the pandemic.Materials and Methods: In the present study, epidemiological characteristics of patients with orthopedic trauma who applied to the emergency department during the COVID-19 year (March 24-July 1, 2020) and the same period of the previous year (March 24-July 1, 2019) were compared. The patients were divided into two groups as pandemic period patients and pre-pandemic group patients (control group). Demographic characteristics, injury mechanisms, fracture types, fracture areas, simultaneous fractures, the locations where the fracture occurred, open fracture types, trauma scores and osteoporosis characteristics were evaluated.Results: 15,245 patients were evaluated, and 36.5% of these patients were the ones who were admitted to our hospital in the pandemic period while 63.5% of the patients were the ones who were admitted to our hospital in the pre-pandemic period. During the pandemic period, 67.2% of the patients visited due to the low-energy traumas, 14.3% high-energy traumas. In the pre-pandemic group, on the other hand, the cause was low-energy traumas in 58.4% of the patients, high-energy traumas in 17.8%. 44% of the patients in the pre-pandemic group and 61% in the pandemic group were evaluated to have osteoporotic fractures. In the pre-pandemic group, on the other hand, 36.2% of the patients had minor, 46.4% serious and 17.4% critical injuries.Conclusion: During the COVID-19 pandemic, because of the effects of long-term inactivity and stress factors, changes were observed in the distribution of the traumatized patients. It should be concluded that people at high risk of osteoporotic fractures should be allowed to practice their physical activities such as walking and exercising at certain time intervals during curfew times such as pandemics.